An Exploration into Occupation-Centered Practice in Skilled Nursing Facilities. (2nd January 2016) - Jewell, Vanessa D.; Pickens, Noralyn D.; Hersch, Gayle; Jensen, Gail
ABSTRACT: Aims: The aims of this pilot study were to identify occupational therapy interventions provided to short-term rehabilitation clients at skilled nursing facilities and to determine if therapists engaged clients in interventions with an occupation-centered approach. Methods: This study utilized a prospective mixed methods design with in-depth observations of two occupational therapists and three clients. Field notes, schematic drawings, and the Occupation-Centered Intervention Assessment documented and captured 57 interventions. Results: Provision of interventions occurred primarily in the clinic (36/57), with exercise and rote practice as the most common intervention approach (26/57), and interventions that utilized occupation were rated higher on the OCIA indicating a more occupation-centered approach. Conclusions: More than half of the interventions did not involve the use or focus on occupation, indicating a gap between theoretical frameworks and interventions taught in professional school and what actually occurs in practice.